Clinical and Esthetic Outcomes of Vestibular Socket Therapy: A Systematic Review and Meta-Analysis - Yasser Sherif Soliman; Nadine Gräfin von Krockow; Fatma E. A. Hassanein; Mihad Ibrahim; Abdelsalam ElAskary; Hossam Ismail (Dentistry Journal, 2026)
Background/Objectives: Vestibular socket therapy (VST) is a minimally invasive technique for immediate implant placement (IIP) in compromised extraction sockets that reconstructs the deficient buccal plate while preserving the crestal soft tissue. Despite growing clinical adoption, the randomized evidence on its predictability and biological performance remains limited. Methods: Following PRISMA 2020 and prospectively registered in PROSPERO (CRD420261288724), PubMed/MEDLINE and EMBASE were searched to January 2026 for randomized controlled trials (RCTs) evaluating VST with IIP. Risk of bias (RoB 2) and certainty of evidence (GRADE) were assessed. Final follow-up buccal bone plate thickness was pooled using a random-effects model; trials comparing variations within VST were reported narratively but not pooled. Results: Seven RCTs (186 participants) were included; implant survival was 99.5%, with no shield exposure, peri-implantitis, or dehiscence. Meta-analysis of the three trials comparing VST against a distinct alternative technique showed no significant between-group difference in final buccal bone plate thickness at any level: crestal +0.24 mm (95% CI−0.13 to 0.61; I2 = 45%), mid-root +0.32 mm (−0.45 to 1.09; I2 = 82%), or apical +0.19 mm (−0.48 to 0.87; I2 = 67%). VST showed minimal mid-facial recession, stable papillae, and Pink Esthetic Scores of 10.29–13.17. Certainty was very low for all outcomes. Conclusions: VST achieved high implant survival and favorable soft tissue and esthetic outcomes but did not significantly outperform comparator techniques in buccal bone plate thickness, with very low certainty. Adequately powered, independent trials with longer follow-up are needed.